Younger Age Is Associated with Poorer Survival in Patients with Signet-Ring Cell Carcinoma of the Colon without Distant Metastasis - Ben Huang; Mengdong Ni; Chen Chen; Yang Feng; Sanjun Cai (Gastroenterology Research and Practice)
Background. In general, younger age is associated with better survival in patients with colon cancer. In this study, we aim to analyze the impact of age on cancer-specific survival (CSS) in patients with signet-ring cell carcinoma (SRCC) of the colon, a particularly aggressive type of colon cancer. Methods. Information on patients with SRCC of the colon with no distant metastasis was extracted from the US Surveillance, Epidemiology, and End Results (SEER) database. An X-tile plot was used to determine the optimal cutoff age at diagnosis. Results. A total of 776 patients were included in data analysis. The X-tile program revealed an optimal cutoff at 35 years of age. A higher percentage of stage III disease and a higher percentage of N2 disease were observed in patients ≤ 35 years of age. The multivariate Cox proportional model demonstrated that patients ≤ 35 years of age were more likely to have a poorer survival outcome compared with patients aged >35 years (HR 1.411, 95% CI 1.032–1.929, and P=0.031). Conclusion. In contrast to the association of younger age with better survival in colon cancer patients, younger age (≤35 years) is associated with poorer survival outcome in patients with SRCC of the colon without distant metastasis.